Sex Ratio and Growth Pattern of Coconut Crabs Birgus latro (Crustacea, Decapoda, Cianobitidae) in North Moluccas Province, Indonesia - Rugaya Serosero; Sulistiono Sulistiono; Nurlisa A. Butet; Etty Riani (Journal Omni-Akuatika, 2019)
Coconut crab (Birgus latro) is a crustacean that has a large size until four kilograms. The study  aimed to analyze sex ratio and growth pattern including the relationship of thorax length - body weight, thorax width - body weight and cephalothorax length plus rostrum - body weight in Daeo (Morotai Island), Laigoma (South Halmahera District) and Fitako (North Halmahera District). The sex ratio was determined using χ2 test and the growth pattern was tested by the b value through t test. The results showed sex ratio of 1: 0.9 in Daeo (n = 581), 1: 0.6 in Laigoma (n = 24), and 1: 2 in Fitako (n = 31). The relationship of thorax length, thorax width and cephalothorax length plus rostrum with body weight were strongly correlated (R2> 70%). The growth pattern of coconut crab in Daeo was negative allometric, while in Laigoma and Fitako were negative allometric and isometric.